Harnessing nighttime transpiration dynamics for drought tolerance in grasses. (3rd April 2021) - López, Jose R.; Schoppach, Rémy; Sadok, Walid
ABSTRACT: Non-negligible nighttime transpiration rates (TRN ) have been identified in grasses such as wheat and barley. Evidence from the last 30 years indicate that in drought-prone environments with high evaporative demand, TRN could amount to 8–55% of daytime TR, leading several investigators to hypothesize that reducing TRN might represent a viable water-saving strategy that minimizes seemingly 'wasteful' water loss that is not traded for CO2 fixation. More recently however, evidence suggests that actual increases in TRN during pre-dawn hours, which are presumably controlled by the circadian clock, mediate drought tolerance – not through water conservation – but by enabling maximized gas exchange early in the morning before midday depression sets in. Finally, new findings point to a previously undocumented role for leaf sheaths as substantial contributors (up to 45%) of canopy TRN, although the extent of their involvement in these two strategies remains unknown. In this paper, we synthesize and reconcile key results from experimental and simulation-based modeling efforts conducted at scales ranging from the leaf tissue to the field plot on wheat and barley to show that both strategies could in fact concomitantly enable yield gains under limited water supply. We propose a simple framework highlighting the role played by TRN dynamics in drought tolerance and provide a synthesis of potential research directions, with an emphasis on the need for further examining the role played by the circadian clock and leaf sheath gas exchange.